High rate of HIV-1 drug resistance in treatment failure patients in Taiwan, 2009–2014 - Tsai, Hung-Chin (Infect Drug Resist, 2017)
BACKGROUND: Drug resistance to nucleoside reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs), and protease inhibitors (PIs) has been associated with loss of viral suppression measured by a rise in HIV-1 RNA levels, a decline in CD4 cell counts, persistence on a failing treatment regimen, and lack of adherence to combination antiretroviral therapy. OBJECTIVES: This study aimed to monitor the prevalence and risk factors associated with drug resistance in Taiwan after failure of first-line therapy. MATERIALS AND METHODS: Data from the Veterans General Hospital Surveillance and Monitor Network for the period 2009–2014 were analyzed. Plasma samples from patients diagnosed with virologic failure and an HIV-1 RNA viral load >1000 copies/mL were analyzed by the ViroSeq(™) HIV-1 genotyping system for drug susceptibility. Hazard ratios (HRs) for drug resistance were calculated using a Cox proportional hazard model. RESULTS: From 2009 to 2014, 359 patients were tested for resistance. The median CD4 count and viral load (log) were 214 cells/μL (interquartile range [IQR]: 71–367) and 4.5 (IQR: 3.9–5.0), respectively. Subtype B HIV-1 strains were found in 90% of individuals. The resistance rate to any of the three classes of antiretroviral drugs (NRTI, NNRTI, and PI) was 75.5%. The percentage of NRTI, NNRTI, and PI resistance was 58.6%, 61.4%, and 11.4%, respectively. The risk factors for any class of drug resistance included age ≤35 years (adjusted HR: 2.30, CI: 1.48–3.56; p<0.0001), initial NNRTI-based antiretroviral regimens (adjusted HR: 1.70, CI: 1.10–2.63; p=0.018), and current NNRTI-based antiretroviral regimens when treatment failure occurs (odds ratio: 4.04, CI: 2.47–6.59; p<0.001). There was no association between HIV-1 subtype, viral load, and resistance. CONCLUSION: This study demonstrated a high level of resistance to NRTI and NNRTI in patients with virologic failure to first-line antiretroviral therapy despite routine viral load monitoring. Educating younger men who have sex with men to maintain good adherence is crucial, as PI use is associated with lower possibility of drug resistance.